Long Non-coding RNA LINC02195 as a Regulator of MHC I Molecules and Favorable Prognostic Marker for Head and Neck Squamous Cell Carcinoma - Li, Hao; Xiong, Hong-Gang; Xiao, Yao; Yang, Qi-Chao; Yang, Shao-Chen; Tang, Hong-Chao; Zhang, Wen-Feng; Sun, Zhi-Jun (Frontiers in Oncology, 2020)
The loss of major histocompatibility complex class I (MHC I) molecules is an important mechanism by which cancer cells escape immunosurveillance in head and neck squamous cell carcinoma (HNSCC). Several long non-coding RNAs (lncRNAs) have been implicated in immune response and regulation including antigen processing and presentation. However, few studies on lncRNAs regulating MHC I expression in HNSCC have been conducted. In this study, MHC I related lncRNAs were identified from the The Cancer Genome Atlas (TCGA) HNSCC database. One of the lncRNAs, long intergenic non-protein coding RNA 2195 (LINC02195), was found to be associated with genes encoding MHC I molecules and patient prognosis in the TCGA database. KEGG and GO analyses suggested that LINC02195 was closely related to antigen processing and presentation. qRT-PCR revealed high expression of LINC02195 in human HNSCC tissues and HNSCC cell lines compared with normal mucosal tissues. In situ hybridization of the HNSCC tissue microarray revealed a correlation between high LINC02195 expression and a favorable prognosis in our patient cohort. Silencing of LINC02195 decreased MHC I protein expression, as evidenced by western blotting. Multiplex immunochemistry was performed to reveal the positive correlation between high LINC02195 expression and an increased number of CD8+ and CD4+ T cells in the tumor microenvironment. Based on our study, LINC02195 is a promising prognostic marker and a target for future therapeutic interventions.